Placental Inflammasome mRNA Levels Differ by Mode of Delivery and Fetal Sex - Arthurs, Anya L.; Smith, Melanie D.; Hintural, Mhyles D.; Breen, James; McCullough, Dylan; Thornton, Francesca I.; Leemaqz, Shalem Y.; Dekker, Gustaaf A.; Jankovic-Karasoulos, Tanja; Roberts, Claire T. (Frontiers in Immunology, 2022)
Parturition signals the end of immune tolerance in pregnancy. Term labour is usually a sterile inflammatory process triggered by damage associated molecular patterns (DAMPs) as a consequence of functional progesterone withdrawal. Activation of DAMPs recruits leukocytes and inflammatory cytokine responses in the myometrium, decidua, cervix and fetal membranes. Emerging evidence shows components of the inflammasome are detectable in both maternal decidua and placenta. However, the activation of the placental inflammasome with respect to mode of delivery has not been profiled. Placental chorionic villus samples from women delivering at term via unassisted vaginal (UV) birth, labouring lower segment caesarean section (LLSCS, emergency caesarean section) and prelabour lower segment caesarean section (PLSCS, elective caesarean section) underwent high throughput RNA sequencing (NextSeq Illumina) and bioinformatic analyses to identify differentially expressed inflammatory (DE) genes. DE genes (IL1RL1, STAT1, STAT2, IL2RB, IL17RE, IL18BP, TNFAIP2, TNFSF10 and TNFRSF8), as well as common inflammasome genes (IL1B, IL1R1, IL1R2, IL6, IL18, IL18R1, IL18R1, IL10, and IL33), were targets for further qPCR analyses and Western blotting to quantify protein expression. There was no specific sensor molecule-activated inflammasome which dominated expression when stratified by mode of delivery, implying that multiple inflammasomes may function synergistically during parturition. Whilst placentae from women who had UV births overall expressed pro-inflammatory mediators, placentae from LLSCS births demonstrated a much greater pro-inflammatory response, with additional interplay of pro- and anti-inflammatory mediators. As expected, inflammasome activation was very low in placentae from women who had PLSCS births. Sex-specific differences were also detected. Placentae from male-bearing pregnancies displayed higher inflammasome activation in LLSCS compared with PLSCS, and placentae from female-bearing pregnancies displayed higher inflammasome activation in LLSCS compared with UV. In conclusion, placental inflammasome activation differs with respect to mode of delivery and neonatal sex. Its assessment may identify babies who have been exposed to aberrant inflammation at birth that may compromise their development and long-term health and wellbeing.